2018
DOI: 10.1103/physrevapplied.9.064026
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Anomalous Spin Torque Generated by a Ferromagnet

Abstract: Over the years central research of spintronics has focused on generating spin-current to manipulate nano-magnets by spin torque. So far electrically 1-9 and thermally driven spin-torques [10][11][12] have been experimentally demonstrated. These torques can be attributed to either Slonczewski's spin-transfer torque (STT) 13 or field-like torque (FLT) 3,8,14 . STT arises when ferromagnet absorbs spin current generated by many ways like spin-Hall effect (SHE) 15,16 , spin-pumping 17 , spin-Nernst effect 18 , spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Some isolate the spin Hall current whose spin direction is transverse to the magnetization [13,14]. Others measure the spin current with a magnetization-aligned spin direction [8][9][10][11]15], as would be expected for bulk spin currents in ferromagnets that have spin directions aligned with the magnetization [21]. Das et al quantify contributions from both transverse and magnetization-aligned spin directions within Py [12], providing experimental evidence supporting some of the results presented here.…”
supporting
confidence: 74%
“…Some isolate the spin Hall current whose spin direction is transverse to the magnetization [13,14]. Others measure the spin current with a magnetization-aligned spin direction [8][9][10][11]15], as would be expected for bulk spin currents in ferromagnets that have spin directions aligned with the magnetization [21]. Das et al quantify contributions from both transverse and magnetization-aligned spin directions within Py [12], providing experimental evidence supporting some of the results presented here.…”
supporting
confidence: 74%
“…For the rest of this Paper, we refer to this SHE as 'conventional SHE.' To combine the virtues of transverse spin transport with magnetic recording, the conventional SHE was studied in magnetic materials with broken TRS (ferromagnets [31][32][33][34][35][36][37][38][39][40][41][42][43][44] or antiferromagnets [30,[45][46][47][48]), which revealed various phenomena associated with the interplay of SOC and magnetism. For example, ferromagnetic metals exhibit an (inverse) conventional SHE [31]; unaffected by magnetization reversal [33] it is time-reversal even.Since charge currents in ferromagnets are intrinsically spinpolarized, transverse AHE currents are spin-polarized as well and are used to generate spin torques [32,35].…”
mentioning
confidence: 99%
“…We have earlier shown that linewidth change can be sensitively measured in planar Hall structure doing ST-FMR [Ref. 32]. We follow the same approach in this work to compare the strength of spin Hall torque (SHT) and spin Nernst torque (SNT).…”
Section: ( )mentioning
confidence: 99%
“…where MS is saturation magnetization, tPt, tPy are thickness of Pt and Py film respectively, H ⊥ is perpendicular magnetic anisotropy field. Now, if dc current is superimposed on the RF current then non-zero dc spin current is injected which can change the resonance linewidth of Py 2,3,32 . It also provides direct quantification of effective spin Hall angle as following:…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation